Hydrogel for periodontitis and preparation method and application thereof

By using hydrogels with composite silver nanoparticles and phenylboric acid graft modified natural polymers in the treatment of periodontitis, the drug resistance of plaque pathogenic bacteria and oxidative damage of periodontitis is solved, and the effective anti-inflammatory and bactericidal effects are achieved, and the treatment of periodontitis is promoted.

CN119792518APending Publication Date: 2025-04-11INST OF BIOLOGICAL & MEDICAL ENG GUANGDONG ACAD OF SCI
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411770727.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing treatment methods for periodontitis cannot effectively solve the problems of frequent colonization of plaque pathogenic bacteria and the emergence of oral drug-resistant bacteria. At the same time, excessive reactive oxygen species in periodontal tissues lead to oxidative stress and tissue damage, making it difficult to effectively treat.

Method used

A hydrogel was developed to form a hydrogel with anti-inflammatory and bactericidal effects by introducing composite silver nanoparticles, benzeneboric acid graft modified natural polymers, polyvinyl alcohol and epigallocatecin gallate. The hydrogel responsively releases nanosilver and epigallocatecin gallate in the oral environment, efficiently removes plaque and regulates the periodontal tissue microenvironment.

Benefits of technology

The hydrogel responsively releases silver and EGCG under ROS stimulation, has excellent anti-inflammatory and bactericidal effects, can effectively remove plaque in conjunction with photothermal effects, and promotes macrophage M2 polarization, achieving efficient treatment of periodontitis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005170205970000081
    Figure BDA0005170205970000081
  • Figure BDA0005170205970000091
    Figure BDA0005170205970000091
  • Figure BDA0005170205970000092
    Figure BDA0005170205970000092
Patent Text Reader

Abstract

The invention discloses hydrogel for periodontitis as well as a preparation method and application thereof, and relates to the technical field of medicines. The hydrogel disclosed by the invention is prepared from composite silver nanoparticles, phenylboronic acid grafted modified natural polymers, polyvinyl alcohol and epigallocatechin gallate, the composite silver nanoparticles comprise polydopamine, epigallocatechin gallate and a silver simple substance; the natural polymer contains a six-membered ring unit, and the six-membered ring unit contains a group which can be oxidized into an aldehyde group. The hydrogel can adapt to the oral environment, responsively releases silver and epigallocatechin gallate under ROS stimulation, has excellent anti-inflammatory and bactericidal effects, is good in photo-thermal activity, can cooperate with the photo-thermal effect to efficiently remove dental plaque, also has the effects of promoting M2 polarization and promoting alveolar bone regeneration, and is especially suitable for treatment of periodontitis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of medicine, and in particular to a periodontitis hydrogel and a preparation method and application thereof. Background Art

[0002] Periodontitis is a chronic infectious disease of the periodontal supporting tissue caused by microorganisms in dental plaque. Its typical characteristics are the loss of periodontal attachment caused by the destruction of the periodontal ligament and the absorption of the alveolar bone. Systemic diseases such as diabetes, Alzheimer's disease, cardiovascular disease, premature birth, rheumatoid arthritis, chronic kidney disease, cancer, and other factors as well as unhealthy lifestyle habits are risk factors for periodontitis. If not treated effectively in time, periodontitis may induce periodontal tissue defects, leading to loose teeth or even tooth loss, greatly reducing the quality of life. At present, the clinical treatment method for periodontitis generally adopts mechanical removal of biofilm supplemented by local or systemic application of antibiotics, but this method cannot effectively solve the problems of frequent colonization of periodontal pathogens and the continuous emergence of oral resistant bacteria.

[0003] At the same time, periodontitis, as a chronic inflammatory disease caused by dental plaque, is characterized by the excessive accumulation of substances such as reactive oxygen species (ROS), which in turn leads to the destruction of periodontal tissues. Excessive ROS in the inflammatory site can cause oxidative stress, creating an inflammatory microenvironment that allows macrophages to maintain the M1 phenotype and release proinflammatory cytokines, thereby exacerbating inflammation. In addition, excessive ROS can directly cause oxidative damage to periodontal tissues by oxidizing cellular lipids and damaging proteins and DNA, making the treatment process more difficult. Therefore, the development of materials with the function of regulating the periodontal tissue microenvironment and high-efficiency antibacterial properties is crucial to the treatment of periodontitis. Summary of the invention

[0004] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, the purpose of the present invention is to provide a hydrogel, which introduces reducing catechol groups and dynamic phenylboronic acid ester bonds into the hydrogel network through the compounding of specific components, can adapt to the oral environment, and responsively release nanosilver and epigallocatechin gallate under ROS stimulation, effectively remove dental plaque, regulate the periodontal tissue microenvironment, and has high antibacterial properties.

[0005] The second aspect of the present invention is to provide a method for preparing a hydrogel.

[0006] The third aspect of the present invention is to provide an application of the hydrogel.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] The first aspect of the present invention provides a hydrogel comprising composite silver nanoparticles, natural polymers grafted and modified by phenylboronic acid, polyvinyl alcohol and epigallocatechin gallate;

[0009] The composite silver nanoparticles include polydopamine, epigallocatechin gallate and silver nanoparticles;

[0010] The natural polymer contains a six-membered ring unit, and the six-membered ring unit contains a group that can be oxidized to an aldehyde group.

[0011] The hydrogel of the present invention contains composite silver nanoparticles, which have excellent antibacterial properties and can efficiently remove dental plaque. At the same time, the hydrogel includes polyvinyl alcohol and epigallocatechin gallate, and epigallocatechin gallate (EGCG) is introduced into polyvinyl alcohol (PVA), and the two can form a uniform system with dynamic hydrogen bonds, and then the catechol on the EGCG and the hydroxyl on the PVA and the phenylboronic acid group on the natural polymer graft-modified by phenylboronic acid form dynamic phenylboronic acid ester chemical bonds, cross-linking into gel, and the composite silver nanoparticles are also uniformly dispersed in the hydrogel network through the action of dynamic phenylboronic acid ester bonds and hydrogen bonds, forming an injectable self-healing adhesive hydrogel with anti-inflammatory and bactericidal effects that can be used to efficiently treat periodontitis.

[0012] In some embodiments of the present invention, the molar content of phenylboronic acid groups in the phenylboronic acid grafted modified natural polymer is 30-50%.

[0013] In some embodiments of the present invention, the molar content of phenylboronic acid groups in the phenylboronic acid grafted modified natural polymer is 35-45%.

[0014] In some embodiments of the present invention, the mass content of silver element in the composite silver nanoparticles is 0.1-0.2%.

[0015] In some embodiments of the present invention, the mass content of silver in the composite silver nanoparticles is 0.1-0.16%.

[0016] In some embodiments of the present invention, the natural polymer includes at least one of hyaluronic acid, sodium alginate, and chondroitin sulfate.

[0017] In some embodiments of the present invention, the hydrogel further comprises a PBS solution.

[0018] During the preparation process of the hydrogel of the present invention, the raw material uses PBS solution as a solvent, and finally a part of the PBS solution remains in the hydrogel.

[0019] In some embodiments of the present invention, the pH of the PBS solution is 7-8.

[0020] In some embodiments of the present invention, the concentration of the PBS solution is 0.08-0.5 mol / L.

[0021] The second aspect of the present invention provides a method for preparing the hydrogel according to the first aspect of the present invention, comprising the following steps:

[0022] The natural polymer modified by phenylboronic acid grafting is dissolved in PBS solution to obtain prepolymer solution A; the mixed solution of polyvinyl alcohol and epigallocatechin gallate is mixed with the composite silver nanoparticle solution to obtain prepolymer solution B;

[0023] The prepolymer solution A and the prepolymer solution B are mixed to obtain the hydrogel.

[0024] In some embodiments of the present invention, the solvents of the polyvinyl alcohol and epigallocatechin gallate mixed solution and the composite silver nanoparticle solution are both PBS solutions.

[0025] In some embodiments of the present invention, the volume ratio of the prepolymer liquid A to the prepolymer liquid B is 1:(0.5-2).

[0026] In some embodiments of the present invention, the volume ratio of the prepolymer liquid A to the prepolymer liquid B is 1:(0.5-1).

[0027] In some embodiments of the present invention, the composite silver nanoparticle solution is a PBS solution of composite silver nanoparticles; the concentration of the composite silver nanoparticle solution is 8-80 mg / mL.

[0028] In some embodiments of the present invention, the concentration of the composite silver nanoparticle solution is 8-15 mg / mL.

[0029] In some embodiments of the present invention, the volume ratio of the polyvinyl alcohol and epigallocatechin gallate mixed solution to the composite silver nanoparticle solution is 1:(0.05-0.5).

[0030] In some embodiments of the present invention, the volume ratio of the polyvinyl alcohol and epigallocatechin gallate mixed solution to the composite silver nanoparticle solution is 1:(0.05-0.25).

[0031] In some embodiments of the present invention, the method for preparing the composite silver nanoparticles comprises the following steps:

[0032] The dopamine hydrochloride solution, the epigallocatechin gallate solution and the soluble silver salt solution are mixed in a solvent, dialyzed and freeze-dried to obtain the composite silver nanoparticles.

[0033] In some embodiments of the present invention, the concentration of dopamine hydrochloride is 0.5-5 mg / mL.

[0034] In some specific embodiments of the present invention, the concentration of dopamine hydrochloride is 0.5-1 mg / mL or 3-5 mg / mL.

[0035] In some embodiments of the present invention, the concentration of the epigallocatechin gallate solution is 0.5-5 mg / mL.

[0036] In some specific embodiments of the present invention, the concentration of the epigallocatechin gallate solution is 0.5-1 mg / mL or 3-5 mg / mL.

[0037] In some embodiments of the present invention, the concentration of the soluble silver salt solution is 13-16 mg / mL.

[0038] In some specific embodiments of the present invention, the soluble silver salt comprises silver nitrate.

[0039] In some embodiments of the present invention, the solvent includes water, aqueous ammonia and ethanol.

[0040] In some specific embodiments of the present invention, the volume ratio of water, aqueous ammonia and ethanol is (22-23):1:10.

[0041] The invention utilizes the self-polymerization of dopamine and epigallocatechin gallate to reduce silver ions in situ, and then further adjusts the reaction ratio, reaction sequence and experimental conditions to prepare and generate stable composite silver nanoparticles in one pot.

[0042] In some embodiments of the present invention, the method for preparing the phenylboronic acid grafted modified natural polymer comprises the following steps:

[0043] The natural polymer, DMTMM and 3-aminophenylboronic acid are dissolved separately to form a solution; after the DMTMM solution and the natural polymer solution are mixed, the 3-aminophenylboronic acid solution is added, and after the reaction, the 3-aminophenylboronic acid solution is dialyzed and freeze-dried to obtain the phenylboronic acid grafted modified natural polymer.

[0044] In some embodiments of the present invention, the natural polymer, DMTMM and 3-aminophenylboronic acid are each dissolved in a PBS solution.

[0045] In some embodiments of the present invention, the pH of the 3-aminophenylboronic acid solution is 6-7.

[0046] In some embodiments of the present invention, the DMTMM solution is first added dropwise to the natural polymer solution, and then the 3-aminophenylboronic acid solution is added.

[0047] In some embodiments of the present invention, the method for preparing the polyvinyl alcohol and epigallocatechin gallate mixture comprises the following steps:

[0048] Polyvinyl alcohol and epigallocatechin gallate are dissolved in PBS solution respectively, and the obtained polyvinyl alcohol solution and epigallocatechin gallate solution are mixed to obtain the polyvinyl alcohol and epigallocatechin gallate mixed solution.

[0049] Since the polyvinyl alcohol solution and the epigallocatechin gallate solution, PVA and EGCG will form hydrogen bonds and crosslink, there will be crosslinked particles when they are mixed unevenly, so during the mixing process of the two, they can be mixed by heating and dissolving and stirring. In some embodiments of the present invention, the temperature of heating and dissolving is 85-95°C.

[0050] In some embodiments of the present invention, the polyvinyl alcohol solution and the epigallocatechin gallate solution are mixed by dropping the epigallocatechin gallate solution into the polyvinyl alcohol solution, with 3 to 6 mL added each time at intervals of 4 to 6 minutes.

[0051] The third aspect of the present invention provides a use of the hydrogel described in the first aspect of the present invention or the hydrogel prepared by the preparation method described in the second aspect of the present invention in preparing a drug for treating periodontitis.

[0052] The hydrogel of the present invention introduces reducing catechol groups and dynamic phenylboron ester bonds through specific components, so that it can adhere to the periodontal target tissue after injection without being damaged by external forces, and adapt to tissue movement, suitable for the special environment of the oral cavity. At the same time, the composite silver nanoparticles are evenly dispersed in the hydrogel network through dynamic phenylboron ester bonds, and silver particles and EGCG are responsively released under the stimulation of excessive periodontal ROS, and the photothermal effect is coordinated to efficiently remove dental plaque. In addition, the reducing catechol groups, ROS-responsive dynamic phenylboron ester bonds, and responsive release of EGCG in the hydrogel can all efficiently remove ROS, which can further promote the polarization and anti-inflammatory of macrophages M2, and achieve efficient treatment of periodontitis.

[0053] Compared with the prior art, the present invention has the following beneficial effects:

[0054] The present invention utilizes composite silver nanoparticles, natural polymer modified by phenylboronic acid grafting, polyvinyl alcohol and epigallocatechin gallate to form a hydrogel, introduces a reducing catechol group and a dynamic phenylboronic acid ester bond, can adapt to the oral environment, and responsively releases silver and epigallocatechin gallate under ROS stimulation, has excellent anti-inflammatory and bactericidal effects, and has good photothermal activity, can synergize the photothermal effect in the oral cavity to efficiently remove dental plaque, and also has the effect of promoting M2 polarization and promoting alveolar bone regeneration. At the same time, the hydrogel can gel quickly, the gelation time is less than 30s, and the preparation method is simple, and is particularly suitable for the treatment of periodontitis. DETAILED DESCRIPTION

[0055] The present invention is further described in detail below by specific examples. Unless otherwise specified, the raw materials, reagents or devices used in the examples and comparative examples can be obtained from conventional commercial sources or can be obtained by prior art methods. Unless otherwise specified, the experiments or test methods are conventional methods in the art.

[0056] The PBS solution used in the following examples of the present invention has a concentration of 0.1 mol / L and a pH of 7.4.

[0057] The present invention is further described in detail below with reference to specific embodiments and comparative examples.

[0058] Example 1

[0059] A method for preparing a hydrogel comprises the following steps:

[0060] Preparation of PDA / EGCG@Ag nanoparticles (composite silver nanoparticles):

[0061] 0.5 mg / mL dopamine hydrochloride aqueous solution, 0.5 mg / mL epigallocatechin gallate (EGCG) aqueous solution and 13 mg / mL AgNO3 solution were slowly added to a mixed solvent of pure water, ammonia water and ethanol (the volume ratio of pure water, ammonia water and ethanol was 22.5:1:10), then stirred at room temperature for 5 h, dialyzed, freeze-dried, and ultrasonically dispersed in PBS at a concentration of 8 mg / mL to obtain a PDA / EGCG@Ag nanoparticle solution, which was stored at 4°C for later use;

[0062] Preparation of phenylboronic acid grafted modified hyaluronic acid:

[0063] 1 g of hyaluronic acid (HA) was dissolved in a mixture of 200 mL of water and DMF (the volume ratio of water to DMF was 1:1) to obtain solution A; 0.5 g of DMTMM was dissolved in a mixture of 4 mL of water and DMF (the volume ratio of water to DMF was 1:1) to obtain solution B; 0.3 g of 3-aminophenylboronic acid (APBA) was dissolved in a mixture of 4 mL of water and DMF (the volume ratio of water to DMF was 1:1), and the pH was adjusted to 6 with a 1 mol / L NaOH solution to obtain solution C; then solution B was added dropwise to solution A, stirred at room temperature for 30 min, then solution C was added, stirred at room temperature for 46 h, dialyzed, and freeze-dried to obtain phenylboronic acid-grafted hyaluronic acid;

[0064] Preparation of PVA / EGCG prepolymer solution (polyvinyl alcohol and epigallocatechin gallate mixture):

[0065] Take 1g of polyvinyl alcohol (PVA) and dissolve it in 80mL PBS, heat and stir at 90℃ for 1h until it is completely dissolved; take 0.5g of epigallocatechin gallate (EGCG) and dissolve it in 18mL PBS, then add the epigallocatechin gallate solution dropwise to the polyvinyl alcohol solution, 3mL each time, with an interval of 5min between each addition, then heat and stir at 90℃ until it is completely dissolved and continue stirring for 20min to obtain PVA / EGCG prepolymer solution;

[0066] Preparation of hydrogel:

[0067] 0.15 g of phenylboronic acid grafted modified hyaluronic acid was dissolved in 10 mL of PBS solution to obtain prepolymer solution A; 10 mL of PVA / EGCG prepolymer solution was taken, and 0.5 mL of PDA / EGCG@Ag nanoparticle solution was added thereto to obtain prepolymer solution B; then prepolymer solutions A and B were fully mixed by vortexing to obtain a hydrogel for periodontitis; wherein the volume ratio of prepolymer solution A to prepolymer solution B was 1:1.

[0068] Example 2

[0069] A method for preparing a hydrogel is different from that of Example 1 in that, in the step of preparing the hydrogel, the amount of the composite silver nanoparticle solution is 0.8 mL; the rest is the same as Example 1.

[0070] Example 3

[0071] A method for preparing a hydrogel is different from that of Example 1 in that, in the step of preparing the hydrogel, the amount of the composite silver nanoparticle solution is 1 mL; the rest is the same as that of Example 1.

[0072] Example 4

[0073] A method for preparing a hydrogel comprises the following steps:

[0074] Preparation of PDA / EGCG@Ag nanoparticles:

[0075] 5 mg / mL dopamine hydrochloride aqueous solution, 5 mg / mL epigallocatechin gallate (EGCG) aqueous solution and 16 mg / mL AgNO3 solution were slowly added to a mixed solvent of pure water, ammonia water and ethanol (the volume ratio of pure water to ammonia water and ethanol was 22.5:1:10, respectively), then stirred at room temperature for 5 h, dialyzed, freeze-dried, and ultrasonically dispersed in PBS at a concentration of 12 mg / mL to obtain a PDA / EGCG@Ag nanoparticle solution, which was stored at 4°C for later use;

[0076] Preparation of phenylboronic acid grafted modified hyaluronic acid:

[0077] 1 g of hyaluronic acid (HA) was dissolved in a mixture of 400 mL of water and DMF (volume ratio of water to DMF was 1.5:1) to obtain solution A; 0.8 g of DMTMM was dissolved in a mixture of 8 mL of water and DMF (volume ratio of water to DMF was 1.5:1) to obtain solution B; 0.6 g of 3-aminophenylboronic acid (APBA) was dissolved in a mixture of 8 mL of water and DMF (volume ratio of water to DMF was 1.5:1) to obtain solution C, and the pH was adjusted to 7 with 1 mol / L NaOH solution to obtain solution C; then solution B was added dropwise to solution A, stirred at room temperature for 30 min, then solution C was added, stirred at room temperature for 46 h, dialyzed, and freeze-dried to obtain phenylboronic acid-grafted modified hyaluronic acid;

[0078] Preparation of PVA / EGCG prepolymer solution:

[0079] 1 g of polyvinyl alcohol (PVA) was dissolved in 120 mL of PBS solution, and the mixture was heated and stirred at 90°C for 1 h until completely dissolved; 0.5 g of epigallocatechin gallate (EGCG) was dissolved in 22 mL of PBS solution, and then the epigallocatechin gallate solution was added dropwise to the polyvinyl alcohol solution, 6 mL was added each time, and the interval between each addition was 5 min. The mixture was heated and stirred at 90°C until completely dissolved, and then the stirring was continued for 20 min to obtain a PVA / EGCG prepolymer solution;

[0080] Preparation of hydrogel:

[0081] 0.15 g of phenylboronic acid grafted modified hyaluronic acid was dissolved in 20 mL of PBS solution to obtain prepolymer solution A; 20 mL of PVA / EGCG prepolymer solution was taken, and 5 mL of PDA / EGCG@Ag nanoparticle solution was added thereto to obtain prepolymer solution B; then prepolymer solutions A and B were fully mixed by vortexing to obtain a periodontitis hydrogel; wherein the volume ratio of prepolymer solution A to prepolymer solution B was 1:1.

[0082] Example 5

[0083] A method for preparing a hydrogel comprises the following steps:

[0084] Preparation of PDA / EGCG@Ag nanoparticles:

[0085] A 3 mg / mL dopamine hydrochloride aqueous solution, a 3 mg / mL epigallocatechin gallate (EGCG) aqueous solution and a 14 mg / mL AgNO3 solution were slowly added to a mixed solvent of pure water, ammonia water and ethanol (the volume ratio of pure water to ammonia water and ethanol was 22.5:1:10, respectively), and then stirred at room temperature for 5 h, dialyzed, freeze-dried, and ultrasonically dispersed in PBS at a concentration of 12 mg / mL to obtain a PDA / EGCG@Ag nanoparticle solution, which was stored at 4°C for later use.

[0086] Preparation of phenylboronic acid grafted modified hyaluronic acid:

[0087] 1 g of hyaluronic acid (HA) was dissolved in a mixture of 300 mL of water and DMF (volume ratio of water to DMF was 1:1) to obtain solution A; 0.5 g of DMTMM was dissolved in a mixture of 6 mL of water and DMF (volume ratio of water to DMF was 1:1) to obtain solution B; 0.5 g of 3-aminophenylboronic acid (APBA) was dissolved in a mixture of 6 mL of water and DMF (volume ratio of water to DMF was 1:1), and the pH was adjusted to 6 with 1 mol / L NaOH solution to obtain solution C; then solution B was added dropwise to solution A, stirred at room temperature for 30 min, then solution C was added, stirred at room temperature for 46 h, dialyzed, and freeze-dried to obtain phenylboronic acid-grafted hyaluronic acid;

[0088] Preparation of PVA / EGCG prepolymer solution:

[0089] 1 g of polyvinyl alcohol (PVA) was dissolved in 100 mL of PBS, and the mixture was heated at 90°C and stirred for 1 h until completely dissolved; 0.5 g of epigallocatechin gallate (EGCG) was dissolved in 20 mL of PBS; then the epigallocatechin gallate solution was added dropwise to the polyvinyl alcohol solution, 4 mL at a time, with an interval of 5 min between each addition, and the mixture was heated at 90°C and stirred for 20 min until completely dissolved, to obtain a PVA / EGCG prepolymer solution;

[0090] Preparation of hydrogel:

[0091] 0.15 g of phenylboronic acid grafted modified hyaluronic acid was dissolved in 15 mL of PBS to obtain prepolymer solution A, 15 ml of PVA / EGCG prepolymer solution was taken, and 3 mL of PDA / EGCG@Ag nanoparticle solution was added thereto to obtain prepolymer solution B; then prepolymer solutions A and B were fully mixed by vortexing to obtain a hydrogel for periodontitis; wherein the volume ratio of prepolymer solution A to prepolymer solution B was 2:1.

[0092] Example 6

[0093] A method for preparing a hydrogel comprises the following steps:

[0094] Preparation of PDA / EGCG@Ag nanoparticles:

[0095] 4 mg / mL dopamine hydrochloride aqueous solution, 4 mg / mL epigallocatechin gallate (EGCG) aqueous solution and 16 mg / mL AgNO3 solution were slowly added to a mixed solvent of pure water, ammonia water and ethanol (the volume ratio of pure water to ammonia water and ethanol was 22.5:1:10, respectively), then stirred at room temperature for 5 h, dialyzed, freeze-dried, and ultrasonically dispersed in PBS at a concentration of 11 mg / mL to obtain a PDA / EGCG@Ag nanoparticle solution, which was stored at 4°C for later use;

[0096] Preparation of phenylboronic acid grafted modified hyaluronic acid:

[0097] 1 g of hyaluronic acid (HA) was dissolved in a mixture of 250 mL of water and DMF (volume ratio of water to DMF was 2:1) to obtain solution A; 0.6 g of DMTMM was dissolved in a mixture of 6 mL of water and DMF (volume ratio of water to DMF was 2:1) to obtain solution B; 0.5 g of 3-aminophenylboronic acid (APBA) was dissolved in a mixture of 6 mL of water and DMF (volume ratio of water to DMF was 2:1), and the pH was adjusted to 7 with a 1 mol / L NaOH solution to obtain solution C; then solution B was added dropwise to solution A, stirred at room temperature for 30 min, then solution C was added, stirred at room temperature for 46 h, dialyzed, and freeze-dried to obtain phenylboronic acid-grafted modified hyaluronic acid;

[0098] Preparation of PVA / EGCG prepolymer solution:

[0099] 1 g of polyvinyl alcohol (PVA) was dissolved in 110 mL of PBS solution, and the mixture was heated and stirred at 90°C for 1 h until completely dissolved; 0.5 g of epigallocatechin gallate (EGCG) was dissolved in 20 mL of PBS, and then the epigallocatechin gallate solution was added dropwise to the polyvinyl alcohol solution, 5 mL each time, with an interval of 5 min between each addition, and the mixture was heated and stirred at 90°C until completely dissolved, and then continued to stir for 20 min to obtain a PVA / EGCG gel prepolymer solution;

[0100] Preparation of hydrogel:

[0101] 0.15 g of phenylboronic acid grafted modified hyaluronic acid was dissolved in 18 mL of PBS to obtain prepolymer solution A, 18 mL of PVA / EGCG prepolymer solution was taken, and 3 mL of PDA / EGCG@Ag nanoparticle solution was added thereto to obtain prepolymer solution B; then prepolymer solutions A and B were fully mixed by vortexing to obtain a hydrogel for periodontitis; wherein the volume ratio of prepolymer solution A to prepolymer solution B was 1:1.

[0102] Comparative Example 1

[0103] A method for preparing a hydrogel, which differs from Example 4 in that the composite silver nanoparticles are replaced with PDA nanoparticles. The preparation method of the PDA nanoparticles is as follows: taking a 4 mg / mL dopamine hydrochloride solution, slowly adding it to a mixed solvent of pure water, ammonia water and ethanol (the volume ratio of pure water to ammonia water and ethanol is 22.5:1:10, respectively), then continuing to stir at room temperature for 5 hours, dialyzing, freeze-drying, and ultrasonically dispersing it in PBS at a concentration of 11 mg / mL and storing it at 4°C for standby use; the rest is the same as Example 4.

[0104] Comparative Example 2

[0105] A method for preparing a hydrogel, which differs from Example 4 in that the composite silver nanoparticles are replaced with EGCG@Ag nanoparticles. The preparation method of the EGCG@Ag nanoparticles is as follows: 4 mg / mL of epigallocatechin gallate (EGCG) solution and 16 mg / mL of AgNO3 solution are slowly added to pure water in sequence, and then stirred at room temperature for 5 hours, dialyzed, freeze-dried, and ultrasonically dispersed in PBS at a concentration of 11 mg / mL and stored at 4°C for use; the rest is the same as Example 4.

[0106] Comparative Example 3

[0107] A method for preparing a hydrogel is different from Example 1 in that composite silver nanoparticles are not prepared and are not added; the rest is the same as Example 1.

[0108] Results

[0109] 1. The gelation time of the hydrogels of Examples 1 to 6 was tested by the inversion method. The gelation time was <30 s, indicating that the hydrogels could gel quickly.

[0110] 2. For Example 1 and Examples 4 to 6, the molar content of phenylboronic acid groups in the phenylboronic acid grafted hyaluronic acid was tested by hydrogen nuclear magnetic resonance spectroscopy, and the mass content of Ag in the composite silver nanoparticles was detected by inductively coupled plasma. The results are shown in Table 1.

[0111] Table 1 Phenylboronic acid group content and Ag content

[0112]

[0113]

[0114] 3. Determine the photothermal activity and bactericidal effect by the plating method. During the measurement, the sample was irradiated with 808nm laser for 10 minutes, and the laser density was 1W / cm 2 .

[0115] The specific process is as follows: 500 μL of the hydrogels of the embodiment and the comparative example were transferred to a 24-well plate, and then 100 μL of Porphyromonas gingivalis (P. gingivalis) suspension (107 CFU mL-1) was added to the surface of the hydrogels, and NIR laser (808 nm, 1 W / cm 2 ) for 10 minutes; after keeping the hydrogel of each embodiment and comparative example in contact with the bacteria for 24 hours, 1 mL of sterile PBS was introduced into each well to resuspend the bacteria; the number of bacteria was determined by the plating method during the process.

[0116] The test results are shown in Table 2.

[0117] Table 2 Photothermal activity and bactericidal effect of hydrogels in Examples and Comparative Examples

[0118]

[0119] From the results shown in Table 2, it can be seen that compared with the hydrogel prepared by the PDA nanoparticles without silver in Comparative Example 1 and the hydrogel prepared by the silver nanoparticles without PDA in Comparative Example 2, which are compared with the hydrogel in Example 4, the hydrogel containing composite silver nanoparticles prepared in Example 4 of the present invention has better photothermal activity under NIR laser irradiation, and can better convert light energy into heat energy, so the temperature is higher after irradiation, and whether or not it is irradiated by laser, the sterilization effect is better than that of Comparative Examples 1 and 2. It can be seen that the hydrogel of the present invention contains composite silver nanoparticles, which has efficient synergistic sterilization performance and excellent photothermal activity.

[0120] 4. Rheology test, cytotoxicity test and periodontitis treatment effect:

[0121] Rheological test: The viscosity changes of the hydrogels of Example 1, Examples 4 to 6 and Comparative Example 3 at different shear frequencies were tested to study the injectability performance, and the self-healing behavior of the hydrogels was evaluated by measuring the recovery of the changes in G' and G" under alternating strain cycles of low strain and high strain; the recovery rate calculation formula is: recovery rate % = G'4 / G'1×100%; G'4 and G'1 represent the storage modulus at low strain in the fourth and first cycles.

[0122] The in vitro drug release performance test was used to test the release time of silver nanoparticles in polydopamine and gel;

[0123] Cytotoxicity was tested by CCK-8 assay;

[0124] Through in vitro macrophage experiments, iNOS / CD206 fluorescence double staining was used to test the changes in M1 and M2 markers. The fluorescence intensity ratio of M2 marker CD206 was calculated between the hydrogel-treated group and the untreated periodontitis group to study the hydrogel-induced M2 polarization effect. The specific treatment method was as follows: RAW 264.7 cells were inoculated in a 24-well plate, 1 μg / mL LPS was added and incubated for 24 hours, then the culture medium was replaced, 100 μL of sterile hydrogel was placed in the middle cavity of the well plate, and culture was continued for 24 hours. Finally, the two markers of M1 and M2, iNOS and CD206, were selected for double immunofluorescence staining.

[0125] Through animal experiments, a rat periodontitis model was established by simple silk suture ligation + high-sugar diet, as follows: weighing, using inhalation gas anesthesia, the rats were fixed in supine position on the experimental table after anesthesia, the maxillary molar group was fully exposed using a homemade opener, the gingiva was separated to the bone surface after disinfection, and a silk thread was inserted into the distal interproximal space of the left maxillary first molar on the palatal side, and then sutured and fixed on the mesial palatal side after surrounding the left maxillary first permanent molar, confirming that the silk thread was not loose and was located in the subgingival position, and checking whether the silk thread was loose every 2 days; after the rat periodontitis model was established, the treatment group was given 30 μL of the corresponding hydrogel, the injection site was located in the gingival sulcus of the left maxillary first molar, and photothermal therapy (808 nm, 1 W / cm 2 ) for 10 minutes, once every 3 days, until 14 days after surgery; then the rats were anesthetized and killed, and the alveolar bone absorption of the hydrogels of Example 1, Examples 4 to 6 and Comparative Example 3 in the left maxillary first molar of the rats was observed and measured by micro-CT, and the distance between the enamel-cementum junction and the alveolar ridge top of the left maxillary first molar (CEJ-ABC distance) was measured, and then the ratio of the treatment group treated with hydrogel to the untreated periodontitis group was calculated, and it was found that the CEJ-ABC value of the periodontitis group was the largest, and the CEJ-ABC value of the treatment group became smaller after alveolar bone regeneration.

[0126] The specific test results of the above test are shown in Table 3.

[0127] Table 3 Rheological properties, cytotoxicity and therapeutic effects of hydrogels on periodontitis

[0128]

[0129]

[0130] From the test results in Table 3, it can be seen that the periodontitis hydrogel prepared in the embodiment of the present invention has injectable, self-healing and tissue adhesion properties, and its cytotoxicity test shows that it is non-toxic, and it is applied to the treatment of periodontitis, and its photothermal activity and high-efficiency antibacterial properties can be used to achieve the treatment of periodontitis. Among them, from the M2 marker fluorescence staining analysis test, it can be seen that the hydrogel of the embodiment can promote M2 polarization, thereby exerting an anti-inflammatory effect and promoting alveolar bone regeneration.

[0131] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A hydrogel, characterized in that: It includes composite silver nanoparticles, natural polymer modified by phenylboronic acid grafting, polyvinyl alcohol and epigallocatechin gallate; The composite silver nanoparticles include polydopamine, epigallocatechin gallate and silver; The natural polymer contains a six-membered ring unit, and the six-membered ring unit contains a group that can be oxidized to an aldehyde group.

2. The hydrogel according to claim 1, characterized in that The molar content of phenylboronic acid groups in the phenylboronic acid grafted modified natural polymer is 30-50%.

3. The hydrogel according to claim 1, characterized in that The mass content of the silver element in the composite silver nanoparticles is 0.1-0.2%.

4. The hydrogel according to claim 1, characterized in that The natural polymer includes at least one of hyaluronic acid, sodium alginate and chondroitin sulfate; And / or, the hydrogel also includes PBS solution.

5. A method for preparing the hydrogel according to any one of claims 1 to 4, characterized in that: The following steps are involved: The natural polymer modified by phenylboronic acid grafting is dissolved in PBS solution to obtain prepolymer solution A; the mixed solution of polyvinyl alcohol and epigallocatechin gallate is mixed with the composite silver nanoparticle solution to obtain prepolymer solution B; The prepolymer solution A and the prepolymer solution B are mixed to obtain the hydrogel.

6. The preparation method according to claim 5, characterized in that: The volume ratio of the prepolymer liquid A to the prepolymer liquid B is 1:(0.5-2).

7. The preparation method according to claim 5 or 6, characterized in that: The composite silver nanoparticle solution is a PBS solution of composite silver nanoparticles; the concentration of the composite silver nanoparticle solution is 8-80 mg / mL; And / or, the volume ratio of the polyvinyl alcohol and epigallocatechin gallate mixed solution to the composite silver nanoparticle solution is 1:(0.05-0.5).

8. The preparation method according to claim 5, characterized in that: The preparation method of the composite silver nanoparticles comprises the following steps: The dopamine hydrochloride solution, the epigallocatechin gallate solution and the soluble silver salt solution are mixed in a solvent, dialyzed and freeze-dried to obtain the composite silver nanoparticles.

9. The preparation method according to claim 8, characterized in that: The concentration of dopamine hydrochloride is 0.5-5 mg / mL; and / or, the concentration of the epigallocatechin gallate solution is 0.5 to 5 mg / mL; and / or, the concentration of the soluble silver salt solution is 13-16 mg / mL; And / or, the solvent includes water, aqueous ammonia and ethanol.

10. Use of the hydrogel according to any one of claims 1 to 4 in the preparation of a drug for treating periodontitis.

Citation Information

Cited By

  • Photocuring hydrogel stent as well as preparation method and application thereof

    CN121287907A